2005
DOI: 10.1303/aez.2005.351
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between developmental stages of rice spikelets and the incidence of the rice bugs Leptocorisa chinensis, Lagynotomus elongatus, and Stenotus rubrovittatus in rice fields

Abstract: To clarify the relationship between the occurrence patterns of three species of rice bugs and the developmental stage of panicles in rice fields, we carried out two experiments. In the first experiment, we observed the development of spikelets in three paddy fields (Plots A, B, and C). The rice variety 'Sainohana' was used in Plot A and 'Koshihikari' was used in Plots B and C. Dates of transplanting were on April 25, May 8, and June 19; for Plots A, B, and C, respectively. Spikelets were classified into three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…Stenotus rubrovittatus is a serious pest of rice, causing pecky rice (Takeuchi et al . ), and migrates from Italian ryegrass and other poaceous plants to rice fields in early summer (Hayashi and Nakazawa ; Kashin et al . ; Nagasawa and Higuchi ).…”
Section: Discussionmentioning
confidence: 99%
“…Stenotus rubrovittatus is a serious pest of rice, causing pecky rice (Takeuchi et al . ), and migrates from Italian ryegrass and other poaceous plants to rice fields in early summer (Hayashi and Nakazawa ; Kashin et al . ; Nagasawa and Higuchi ).…”
Section: Discussionmentioning
confidence: 99%
“…3). Takeuchi et al (2005a) reported that immigrant peaks of adult L. chinensis in rice fields were observed from 100 to 150 degree-days after the initial heading stage. These results suggested that the immigration of L. chinensis did not occur in the field where the grass plants did not bear seed head, even the dispersal of L. chinensis from hibernation sites had already begun.…”
Section: Effects Of Temperaturementioning
confidence: 99%
“…Although S. rubrovittatus shows an opportunistic tactic (i.e., polyphagy and multivoltine brood strategy), the bug exhibits a marked preference to L. multiflorum inflorescences from early to midsummer, when the plant species produces seed heads ( Yoshioka et al 2011 ). The mirid bug, however, only occurs in rice paddies during the short period when rice heads are present in midsummer ( Takeuchi et al 2005 ). They reproduce little in rice paddies ( Takeuchi et al 2005 ) but are assumed to spill over to rice fields from proximal meadows and fallow fields dominated by L. multiflorum .…”
Section: Introductionmentioning
confidence: 99%
“…The mirid bug, however, only occurs in rice paddies during the short period when rice heads are present in midsummer ( Takeuchi et al 2005 ). They reproduce little in rice paddies ( Takeuchi et al 2005 ) but are assumed to spill over to rice fields from proximal meadows and fallow fields dominated by L. multiflorum . Therefore, meadows can be regarded as source habitats for the bugs, and the paddies are sinks.…”
Section: Introductionmentioning
confidence: 99%